Safeguards Assessments : Review of Experience. (Policy Papers; Policy Paper ;, 2010)
This paper presents the Fund's net income outcome for FY 2010. The actual outcomes in this paper follow the closing of the Fund's accounts for the financial year and completion of the FY 2010 external audit conducted by Deloitte and Touche, the Fund's external auditor. The paper also provides an update on the restructuring costs incurred during FY 2010.